A Regulamentação dos Empregados Domésticos no Brasil face aos Princípios da Igualdade e da Dignidade da Pessoa Humana: as perspectivas da Convenção N. 189 da OIT e da PEC 478/2010 - Capistrano, Kássia Líriam de Lima Costa (2013)
The domestic workers are marked by the social segregation, which has followed them since their origin, which is, slavery. It is noticeable that the social alternatives propitiated them gradual conquer of freedom, which in order to be in effect demands promotion of substantial equality. The conjunction of the preservation of the principles of freedom and equality, understood in its integral dimensions, will result in the personal development of the individual, which will turn into the builder agent of the society to the extent in which it will acquire potentiality. Next, the development of the human being collaborates for the well being of others, desideratum of the Federal Constitution. In the elapse of the study, it will be found that the Principle of Dignity of the Human Being is operated as a matrix and as the goal of the whole Constitution. Therefore, collimating the Constitution, the dignified labor comes up as a preponderant factor, urging on the ruling of diverse supranational debates. Suggesting the necessity to guarantee the domestic workers a decent labor, tuned with the values referenced in the Human Rights, the OIT launched a proposal at the Convention N. 189 of the OIT, of matching the rights of the domestic workers to the ones already granted to other categories of workers. With the approval of this proposal, the PEC N. 478/2010 made a comeback and already follows its ordinary legislative process to the Senate. It is noted that the proposal mentioned in PEC N. 478/2010 converges with the one already listed by the Convention N 189 of OIT. The scope of this paper is to demonstrate the feasibility of access of Brazil to the alluded proposals, utilizing historic, statistical, doctrinal and legal fundamentals, especially the standards inserted inside the Magna Carta.